Application of "LitAr" material in glaucoma surgery in children and adults - R. L. Troyanovsky; S. N. Solonina; N. A. Malinovskaya; A. V. Baranov; S. D. Litvinov; A. S. Golovin; M. A. Kleshchev; S. N. Mednikov; E. V. Sineok (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
The success of surgical treatment of glaucoma, stabilization and preservation of visual functions are fundamentally dependent on the steady normalization of the eye hydrodynamics. The problem of refractory, resistant to glaucoma treatment in children and adults, including congenital glaucoma, remains extremely urgent. The article presents the results of glaucoma treatment, including refractory and buffalma glaucoma, using polymer-salt material "LitAr". The proposed composite proved to be useful both for planned application and in case of buftalma to provide fast remission and improvement of vision. An important fact is that the polymer-salt material "LitAr" has been successfully used both in primary operations and corrective interventions in patients with resistant to treatment glaucoma.